Hybrid Generalized Estimator for Power Systems - Ahmed Abdolkhalig (Aljameai, 2024)
Abstract: a state estimation in Power Systems is the procedure of estimating the states of voltage magnitude and angle at all buses based on the availability of measurements. Traditionally, the Supervisory Control and Data Acquisition (SCADA) system was able to provide all quantities measured in addition to the statuses of all system switches. More recently, a measuring device called a phasor measurement unit (PMU) which can dynamically measure the phasors (both magnitude and angle) of voltage and current of a bus at which it is installed. This device is capable of measuring any dynamic changes in the phasors. Adding more PMUs to the system will improve the time-skew errors in the power system. In this paper, the improvement in the state estimation using the quantities measured by PMU has been explained. The improvement is validated for IEEE-14 bus and IEEE-30 bus systems. The proposed state estimator utilizes estimated states from the Weighted Least Square (WLS) model in addition to estimated states from PMU-function which is modeled based on Kalman filtering. The estimation is done firstly in polar formation by using the WLS model from conventional measurements then, these states from the PMU function are both used to estimate the final system state estimation expressed in rectangular coordinates. The MATLAB program has been used for simulation and verification results.المستخلص:تقدير الحالة في أنظمة الطاقة هو إجراء تقدير حالات حجم الجهد والزاوية في جميع الناقلات بناءً على توفر القياسات. تقليديًا، كان نظام التحكم الإشرافي والحصول على البيانات (SCADA) قادرًا على توفير جميع الكميات المقاسة بالإضافة إلى حالات جميع محولات النظام. في الآونة الأخيرة، تم تطوير جهاز قياس يسمى وحدة قياس الطور (PMU) والذي يمكنه قياس أطوار (المقدار والزاوية) للجهد والتيار للموصل الذي تم تركيبه عليها ديناميكيًا. هذا الجهاز قادر على قياس أي تغيرات ديناميكية في الأطوار. ستؤدي إضافة المزيد من هذه الوحدات إلى النظام إلى تحسين أخطاء الانحراف الزمني في نظام الطاقة. في هذه الورقة، تم شرح التحسن في تقدير الحالة باستخدام الكميات المقاسة بواسطة هذه الوحدات.  تم التحقق من صحة التحسين لأنظمة الناقلات IEEE-14 وIEEE-30.  يستخدم مقدر الحالة المقترح الحالات المقدرة من نموذج المربع الأصغر المرجح (WLS) بالإضافة إلى الحالات المقدرة من وحدات  PMU التي تم تصميمها على أساس مرشح كالمان. يتم التقدير أولاً في التكوين القطبي باستخدام نموذج WLS من القياسات التقليدية، ثم يتم استخدام هذه الحالات من وظيفة PMU لتقدير تقدير حالة النظام النهائي المعبر عنه في الإحداثيات المستطيلة. تم استخدام برنامج MATLAB للمحاكاة والتحقق من النتائج.